Influence of minimum quantity lubrication on surface integrity of ground hardened H13 hot die steel - Awale A.S.; Srivastava A.; Vashista M.; Khan Yusufzai M.Z. (My University, 2025)
In grinding process, cutting fluids play an important role to control high grinding zone temperature. However, their use causes detrimental effect on the operator’s health and environment. On the other hand, dry grinding not only results in thermal damage to ground surface but also deteriorates the surface quality and dimensional accuracy of the ground component. The possible solution is to apply cutting fluids using minimum quantity lubrication (MQL) technique. The objective of present research work is to investigate and compare the effect of different grinding environments: dry, flood, MQL with deionized water (DIW), MQL with liquid paraffin oil (LP), and MQL with castor oil based on vegetable oil (VO) during grinding of hardened H13 hot die steel. Grinding performance was evaluated in terms of specific grinding force, specific grinding energy, grinding force ratio, surface roughness, and microhardness. Ground surface and debris morphology were also analyzed using scanning electron microscope, atomic force microscope, and energy-dispersive X-ray spectroscopy to validate the grinding performance. The results showed that MQL-VO grinding leads to minimum specific grinding force, specific grinding energy, and grinding force ratio. Further, surface roughness was considerably reduced under MQL-VO grinding, where Rɑ and Rz were 0.245 μm and 1.846 μm, respectively. AFM analysis indicated that the surface roughness of MQL-VO grinding was nearly 29.88% less as compared to dry grinding. Smooth ground surface topography, as well as long, thin, and no wear track grinding debris, were observed under MQL-LP and MQL-VO conditions. Moreover, dry grinding resulted in lower microhardness in comparison to other grinding conditions. © 2018, Springer-Verlag London Ltd., part of Springer Nature.